2019
DOI: 10.1039/c9fo00460b
|View full text |Cite
|
Sign up to set email alerts
|

Monofloral honey from a medical plant,Prunella Vulgaris, protected against dextran sulfate sodium-induced ulcerative colitisviamodulating gut microbial populations in rats

Abstract: Honey produced from medicinal plants hold great promise for human gut health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 44 publications
1
80
0
Order By: Relevance
“…The underlying mechanisms are that sebocytes can be recognized and activated by P. acnes , which further trigger the release of inflammatory cytokines [ 39 ]. TNF- α is an extensively studied cytokine associated with many inflammatory diseases [ 40 ]. Evidences indicated that IL-1 α is one of the main inflammatory factors, which could induce the proliferation of keratinocytes and sebaceous gland cells and eventually promote the formation of acne vulgaris [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms are that sebocytes can be recognized and activated by P. acnes , which further trigger the release of inflammatory cytokines [ 39 ]. TNF- α is an extensively studied cytokine associated with many inflammatory diseases [ 40 ]. Evidences indicated that IL-1 α is one of the main inflammatory factors, which could induce the proliferation of keratinocytes and sebaceous gland cells and eventually promote the formation of acne vulgaris [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal barriers are important for the body's resistance to external pathogens and toxins, inflammation, stress, surgical trauma, and hypovolemia; however, ischemia-reperfusion injury can cause intestinal barrier damage [93,94]. Thus, bacteria and toxins in the intestine can reach the mesenteric lymphoid tissues, lymph fluid, blood, and extraintestinal tissues and organs, causing gut-derived sepsis and eventually leading to multiple organ dysfunction syndrome (MODS) [95].…”
Section: Intestinal Protectionmentioning
confidence: 99%
“…Anthocyanins have been reported to increase the relative abundance of beneficial bacteria such as Bifidobacterium and Akkermansia, which are believed to be closely related to anti-inflammatory effects [24,65]. Monofloral honey from Prunella Vulgaris, rich in PCA, VA, and FA, showed protective effects against dextran sulfate sodium-induced ulcerative colitis in rats potentially through restoring the relative abundance of Lactobacillus [66]. Our previous studies also found that the Lonicera caerulea L. berry rich in C3G could attenuate inflammation potentially through the modulation of gut microbiota, especially the ratio of Firmicutes to Bacteroidetes in a mouse model of experimental non-alcoholic fatty liver disease [67].…”
Section: Crosstalk Between Gut Microbiota and C3gandc3g-msmentioning
confidence: 99%